The Influence of the Quality Physical Conditions on Chess Athlete for the Achievement of the National Paralympics - Nasir, Haidar; Imanudin, Iman; Hardwis, Syam (STKIP Pasundan, 2025)
This study aims to analyze the influence of physical condition quality on the performance of chess athletes with disabilities at the 2024 National Paralympic Games (PEPARNAS) in West Java. Employing a quantitative approach, the study involved 21 chess athletes competing in individual and team categories. Physical condition data were collected through the Sit and Reach test for flexibility and the Balke test for aerobic endurance, while performance was measured based on medal achievements. Linear regression analysis revealed that flexibility and aerobic capacity accounted for only 0.1% of the variation in individual performance (R² = 0.001, p = 0.991) and 5.9% of the variation in team performance (R² = 0.059, p = 0.576), indicating that these variables had no significant impact on chess performance. These findings confirm that chess relies more on cognitive and strategic abilities than physical condition.